PENGARUH PERCAVA DIRI DAN KOMPETENSI PROFESIONAL TERHADAP KOMITMEN AFEKTIF DIMODERASI OLEH KEPEMIMPINAN IDEALIZED INFLUENCE (Studi pada guru SMP Negeri seKawedanan Bandar Kabupaten Batang) - Raharjo, Muji; Liana, Lie (Jurnal Ilmiah Telaah Manajemen, 2017)
This research aims to analyze the influence of self confidence, professional competence and idealized influence leadersiup to aifretive cummilmc’nl and the rok uf ickallzt’d in/luence kadership moderated tite influence of self confidence and pivfessional competence on a(frciive comrnitnwnt to the teacher of vocational secondary school in Barang Regency. This research uses explanatory rcwucrh. The populations in of the research are the teacher of y,cat,onal secondary school in Batang Regency. they are 120 people. Based lest validity, KMO in all variables of the model ¡n this stuth’ is greater ¡han 0., this is indicate that the sample is adequacy. The loading factor in all indicators t1ai used in this rescach is larger titan 0.4 and the value of’ Alpha cronhach is greater thais 0, 7. This means thai all indicators valid and reliahihtv. According so the data of Oiw-Sample Kobnogorov—Smirnov Test regression models to Normal and no l!eieroskedasticitv. Based on the hypothesis tes!, one of the kpothesis is accepted and four hypothesis are re/ected The results are self confidence has not effect on affrctive commitment, professional competence has positive efii’ct on affective commitment, idealized influence leadership has not effect on aljective commitment, idealized influence leadership does not moderate tite influence ‘ cell confidence on affective conunitme’nt,j idealized influence leadership does not moderate the influence ofprofrs.cs anal conspetence on affective co?nmitment.